Development and application of a quadruplex real-time PCR method for Torque teno sus virus 1, Porcine circovirus type 2, pseudorabies virus, and porcine parvovirus - Quan, Fushi; Geng, Yulu; Wu, Yang; Jiang, Faming; Li, Xuemei; Yu, Changqing (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionIn clinical diagnosis of porcine diseases, co-infection with multiple viruses often leads to similar clinical symptoms. Postweaning multisystemic wasting syndrome (PMWS) can be caused by infections with TTSuV or PCV2, while PCV2, PRV, and PPV can cause respiratory and reproductive disorders in pigs. The overlapping clinical and pathological features of these infections necessitate the development of a rapid and specific method for differentiating and detecting these four DNA viruses.MethodsIn this study, four pairs of primers and TaqMan probes were designed targeting the conserved sequence of TTSuV, the Rep gene of PCV2, the gE gene of PRV, and the VP2 gene of PPV. After optimizing reaction conditions, including annealing temperature, primer concentration, and probe concentration, a quadruplex real-time PCR method was developed.ResultsThis method can specifically detect TTSuV1, PCV2, PRV, and PPV simultaneously, with no cross-reactivity with ASFV, CSFV, PRRSV, PEDV, PSV, and TGEV. The minimum detection limit for each virus was 10 copies/μl, and the inter-assay and intra-assay coefficients of variation ranged from 0.33% to 1.43%. Subsequently, 150 clinical samples were tested to evaluate the practical applicability of this method. The positive rates for TTSuV1, PCV2, PRV, and PPV were 8.6% (13/150), 10.67% (16/150), 14% (21/150), and 11.33% (17/150), respectively.DiscussionThe results indicate that the established quadruplex real-time PCR method can assist in the accurate and rapid diagnosis of TTSuV1, PCV2, PRV, and PPV in clinical settings, providing robust support for the prevention and control of these infections.